1997
DOI: 10.1143/jjap.36.l330
|View full text |Cite
|
Sign up to set email alerts
|

Capacitance Anomaly in the Negative Differential Resistance Region of Resonant Tunneling Diodes

Abstract: For In0.53Ga0.47As/AlAs resonant tunneling diodes, the peak structure in the capacitance-voltage ( C-V) characteristics in the negative differential resistance (NDR) region was investigated. We experimentally reveal that the electron sheet density that is responsible for the capacitance peak is equal to half of that in the quantum well at the peak voltage. The derived electron sheet density in the quantum well at the peak current is 3.2×1011 cm-2 and the resulting electron lifetimes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…The total change of the frequency was typically 1-5%. The mechanism of this change is the bias-dependent tunneling time, which produces the bias-dependent additional capacitance and the frequency change [57,58,59,60,61]. This frequency change was also observed in the RTD oscillating above 1 THz shown in Fig.…”
Section: Spectral Characteristics and Direct Modulationmentioning
confidence: 64%
“…The total change of the frequency was typically 1-5%. The mechanism of this change is the bias-dependent tunneling time, which produces the bias-dependent additional capacitance and the frequency change [57,58,59,60,61]. This frequency change was also observed in the RTD oscillating above 1 THz shown in Fig.…”
Section: Spectral Characteristics and Direct Modulationmentioning
confidence: 64%
“…Table I shows these parameters used in our simulations. The capacitance per unit area, C 0 , was assumed to be 2 fF/mm 2 in accordance with Shimizu et al 14) The simulated I-V curve is shown in Fig. 2.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The value of Γ between doped/undoped layers dictates the shape of the IV-characteristic [37]; a low value, perhaps counter-intuitively, lowers the current density, but sharpens the NDR drop (triangle or Z-shaped I-V curve), whilst a high value increases the current density and lowers the slope of the NDR (smooth N-shape I-V curve). To further improve the fit quality, the device active region (area where the Fermi-equivalent potential is tilted) needs a careful selection such that the charge stored in the QW corresponds to those estimated by Shimizu et al [43]. Whilst the modelled voltage-dependent capacitance is a chief parameter required in predicting the gain bandwidth of the device, this remains a subject to be covered in more detail in future work.…”
Section: Methodsmentioning
confidence: 99%